Research Hot Spots, Trends and Prospects of China’s Global Discourse System: A Bibliometric Analysis Based on the CNKI Database (2012–23) (World Marxist Review, 2025)
In this transformative epoch, China occupies an indispensable strategic position in the construction of the global discourse system, with its international discursive power steadily reaching new heights. Against this backdrop, the construction of the global discourse system has emerged as of paramount importance. This article analyzes by means of bibliometrics the overall trend and disciplinary distribution of academic publications based on the data of core journals from CNKI from 2012 to 2023. By means of a co-word analysis, we find that keywords such as “community with a shared future for humanity” “scientific outlook on development” “holistic national security,” “national security” “ecological civilization” “socialism with Chinese characteristics” and “Communist Party of China” constitute the main topics in China’s global discourse system. Looking ahead, it is necessary to investigate thoroughly the essence of the best of traditional Chinese culture, systematically analyze the rich connotations of Marxist philosophy, and also emphasize deepening comparative studies from a dual perspective of China and the West, with the aim of achieving innovative development in China’s global discourse system.